A COMPARATIVE STUDY ON THE RECOGNITION OF THE RELIGION IN THE INDIGENOUS PEOPLE COMMUNITY IN INDONESIA ACCORDING TO THE CONSTITUTIONAL COURT DECISIONS NUMBER 97/PUU-XIV/2016 AND 140/PUU-VII/2009 - Sihombing, Uli Parulian; Safa'at, Muchammad Ali; Setya Negara, Tunggal Ashari; Widiarto, Aan Eko (Tadulako Law Review, 2020)
This article is intended to conduct a legal research on how the constitutional courts have interpreted the meaning of the religion in the constitution of Indonesia. The author has applied normative legal reseach method by compiling and analyzing the constititonal court decisions related to the issue of the religios in the indigenous community in Indonesia. Also, the author try to raise a statutory approach and legal reasonings in the constitutional court decision to analyse the legal issues. According to the result of this legal research, the author comes to the following conclussions; the constitutional court decisions has applied and used the historic interpretation method of a religion meaning in the constitution, but the constitutional courts have come to the different result of the religion meaning in the constitution. While the constitutional court decision number 140/PUU-VII/2009 excluded the meaning of the religion in the constitution, however, the constitutional court decision number 97/PUU-XIV/2016 embarced the meaning of the religion in the constitution.